Coating two-dimensional nanomaterials with metal-organic frameworks - Huang, Xiao (2014)
We demonstrate the coating of various 2D nanomaterials including MoS2 nanosheets, graphene oxide (GO), and reduced graphene oxide (rGO) with zeolitic imidazolate frameworks (i.e., ZIF-8) via a facile procedure. Additionally, ternary core–shell structures like Pt-MoS2@ZIF-8, Pt-GO@ZIF-8, and Pt-rGO@ZIF-8 have also been prepared. As a proof-of-concept application, a memory device based on MoS2@ZIF-8 hybrid was fabricated and it exhibited write-once-read-many-times (WORM) memory effect with high ON/OFF ratio and long operating lifetime. It is expected that MOF coated 2D nanomaterials may find wide applications in energy storage and conversion, catalysis, sensing, and information storage devices.